Education, best inheritance or best business? Educational segregation in Peru and the challenges for citizenship education (Revista Peruana de Investigación Educativa, 2021)
There is a strong and increasing trend towards educational segregation in Peru, making it one of the most unequal educational systems in the region. Educational segregation is evidenced by higher homogeneity in students’ characteristics in each school, in a system where privatization is growing along with the spread of educational institutions of diverse quality. This article put in dialogue studies on educational segregation in Peru and analyzes two cases of educational policy that far from mitigate, intensify educational segregation of the educational system. The paper also reflects on the challenges that segregation poses for the quality of the educational system itself, for equity and for the forging of democratic citizenship. It considers how the families’ educational aspirations develop amidst a context that favors privatization and naturalization of social inequalities.
Keywords: educational segregation, Peru, educational policy, equity